Ticagrelor versus clopidogrel in elderly patients with acute coronary syndromes - Husted, Steen Elkjær; Katus, Hugo (Circulation. Cardiovascular quality and outcomes, 2012)
Background—Elderly patients with acute coronary syndrome are at high risk of recurrent ischemic events and death, and for both antithrombotic therapy and catheter-based complications. This prespecified analysis investigates the effect and treatment-related complications of ticagrelor versus clopidogrel in elderly patients (≥75 years of age) with acute coronary syndrome compared with those <75 years of age.Methods and Results—The association between age and the primary composite outcome, as well as major bleeding were evaluated in the PLATelet inhibition and patient Outcomes (PLATO) trial using Cox proportional hazards. Similar models were used to evaluate the interaction of age with treatment effects. Hazard ratios were adjusted for baseline characteristics. The clinical benefit of ticagrelor over clopidogrel was not significantly different between patients aged ≥75 years of age (n=2878) and those <75 years of age (n=15 744) with respect to the composite of cardiovascular death, myocardial infarction, or stroke (interaction P=0.56), myocardial infarction (P=0.33), cardiovascular death (P=0.47), definite stent thrombosis (P=0.81), or all-cause mortality (P=0.76). No increase in PLATO-defined overall major bleeding with ticagrelor versus clopidogrel was observed in patients aged ≥75 years (hazard ratio, 1.02; 95% confidence interval, 0.82-1.27) or patients aged <75 years (hazard ratio, 1.04; 95% confidence interval, 0.94-1.15). Dyspnea and ventricular pauses were more common during ticagrelor than clopidogrel treatment, with no evidence of an age-by-treatment interaction.Conclusions—The significant clinical benefit and overall safety of ticagrelor compared with clopidogrel in acute coronary syndrome patients in the PLATO cohort were not found to depend on age.Clinical Trial Registration—URL: http://www.clinicaltrials.gov. Unique identifier: NCT00391872.
Gesehen am TT.MM.JJJ